Outcomes and Conditions of Project-Based Learning in Higher Education: An International Systematic Review - Valenzuela Averruz, Tanya Walkiria; Naranjo Iturralde, Carlos Héctor (Scientific journal of social studies, 2026)
This article presents a systematic review of scientific literature on Project-Based Learning (PBL) in higher education, aiming to analyze its outcomes, limitations, and implementation conditions in the international context during the period 2015–2025. The review followed search, selection, and analysis procedures inspired by PRISMA 2020. EBSCO, ERIC, DOAJ, Redalyc, and SciELO were consulted, with Google Scholar used as a complementary source. After record screening and the application of inclusion and exclusion criteria, 53 studies were selected. The methodological quality of empirical studies was assessed using the MMAT, while non-empirical documents were examined through an ad hoc documentary rigor matrix. Findings were organized into four analytical axes: student experience, teacher experience, methodologies, and institutional dimension. Results show that PBL tends to enhance academic performance, motivation, autonomy, collaboration, and the connection between theory and practice, although its effects are not uniform across contexts. Its effectiveness depends on the quality of teaching mediation, the methodological design of the project, and institutional support. The study concludes that PBL is not an automatic pedagogical solution, but rather a strategy whose transformative potential depends on specific pedagogical, curricular, and organizational conditions.
Keywords: higher education; Project-based learning; systematic review; teaching practice; student experience; institutional conditions